2017
DOI: 10.1038/onc.2016.504
|View full text |Cite
|
Sign up to set email alerts
|

A double-negative feedback loop between EpCAM and ERK contributes to the regulation of epithelial–mesenchymal transition in cancer

Abstract: Epithelial-mesenchymal transition (EMT) is an important biologic process that has been implicated in cancer metastasis. Epithelial cell adhesion molecule (EpCAM) is expressed at the basolateral membrane of most normal epithelial cells, but is overexpressed in many epithelial cancers. In our studies of the role of EpCAM in cancer biology, we observed that EpCAM expression is decreased in mesenchymal-like primary cancer specimens in vivo, and following induction of EMT in cancer cell lines in vitro. Extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 58 publications
4
76
1
Order By: Relevance
“…Induction of EpCAM results in various cellular outcome including cell-cell adhesion 37 , enhanced tumor cell proliferation 19 , 38 and regulation of stem cell features 20 , 39 41 . Itself, EpCAM is prone to substantial regulation throughout cancer progression 27 , 42 , 43 , stem cell differentiation 22 , and during EMT related to treatment resistance, e . g .…”
Section: Discussionmentioning
confidence: 99%
“…Induction of EpCAM results in various cellular outcome including cell-cell adhesion 37 , enhanced tumor cell proliferation 19 , 38 and regulation of stem cell features 20 , 39 41 . Itself, EpCAM is prone to substantial regulation throughout cancer progression 27 , 42 , 43 , stem cell differentiation 22 , and during EMT related to treatment resistance, e . g .…”
Section: Discussionmentioning
confidence: 99%
“…The ERK pathway has been implicated in malignant transformation and in the regulation of cellular proliferation and metastasis of several tumor types . Furthermore, we found that overexpression of CD44s increased ERK1/2 activation in HCC cells (Figure ).…”
Section: Resultsmentioning
confidence: 67%
“…EMT is a key step toward cancer metastasis . Wnt, TGF‐β, Notch, NF‐κB, and MAPK/ERK have been implicated as the key pathways involved in EMT process. Several lncRNAs participate in EMT process .…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In this study, a novel lncRNA, lncRNA DRHC, was shown to be EMT is a key step toward cancer metastasis. 26 Wnt, 27 TGF-β, 28,29 Notch, 30,31 NF-κB, 32,33 and MAPK/ERK 34 have been implicated as the key pathways involved in EMT process. Several lncRNAs participate in EMT process.…”
Section: Discussionmentioning
confidence: 99%